Potential application of Saccharomyces boulardii as a probiotic in goat's yoghurt: survival and organoleptic effects - Karaolis, Constantinos; Pantelides, Iakovos S; Tsaltas, Dimitrios; Botsaris, George (My University, 2013)
Potential application of Saccharomyces boulardii in yoghurts could offer an alternative probiotic product to people suffering from antibiotic-associated diarrhoea whilst on treatment. Three different yoghurts were made using goat's milk. Yoghurt 1 was the control with only starter culture added to the milk. For Yoghurt 2, S. boulardii was added in parallel with the starter culture, and for Yoghurt 3, the yeast was added after the yoghurt was coagulated by the starter. Duplicate counts for lactic acid bacteria (LAB) and S. boulardii alongside organoleptic assessment were carried out every 3 days following manufacture and storage at 6 °C. Our results demonstrate that S. boulardii can survive in high numbers for the period of 4 weeks tested without significant changes in taste. Very important is the fact that the presence of the yeast stimulated the survival of the LAB, which in both yeast yoghurts were significantly higher than in the control.
Keywords: Probiotics; Diarrhea; Open access publishing